The dynamics of the hotel customer - Carvell, Pamela (Henry Stewart Talks, 2009)
Defining the target market, Market segments, Individual business traveller, Individual leisure traveller, Leisure groups, Meetings, Wedding guests, Complexity of the decision making process, Influencing customer choice, Marketing focus